Targeting CTP synthetase 1 to restore interferon induction and impede nucleotide synthesis in SARS-CoV-2 infection - Youliang Rao; Chao Qin; Bianca Espinosa; Ting-Yu Wang; Shu Feng; Ali Can Savas; Jill Henley; Lucio Comai; Chao Zhang; Pinghui Feng (mBio)
ABSTRACT Despite the global impact caused by the most recent SARS-CoV-2 pandemic, our knowledge of the molecular underpinnings of its highly infectious nature remains incomplete. We report here that SARS-CoV-2 exploits cellular CTP synthetase 1 (CTPS1) to promote CTP synthesis and suppress interferon (IFN) induction. In addition to catalyzing CTP synthesis, CTPS1 also deamidates interferon regulatory factor 3 (IRF3) to dampen interferon induction. Screening a SARS-CoV-2 expression library, we identified several viral proteins that interact with CTPS1. Functional analyses demonstrate that ORF8 and Nsp8 activate CTPS1 to deamidate IRF3 and negate IFN induction, whereas ORF7b and ORF8 activate CTPS1 to promote CTP synthesis. These results highlight CTPS1 as a signaling node that integrates cellular metabolism and innate immune response. Indeed, small-molecule inhibitors of CTPS1 deplete CTP and boost IFN induction in SARS-CoV-2-infected cells, thus effectively impeding SARS-CoV-2 replication and pathogenesis in mouse models. Our work uncovers an intricate mechanism by which a viral pathogen couples immune evasion to metabolic activation to fuel viral replication. Inhibition of the cellular CTPS1 offers an attractive means to develop antiviral therapy against highly mutagenic viruses.IMPORTANCEOur understanding of the underpinnings of highly infectious SARS-CoV-2 is rudimentary at best. We report here that SARS-CoV-2 activates CTPS1 to promote CTP synthesis and suppress IFN induction, thus coupling immune evasion to activated nucleotide synthesis. Inhibition of the key metabolic enzyme not only depletes the nucleotide pool but also boosts host antiviral defense, thereby impeding SARS-CoV-2 replication. Targeting cellular enzymes presents a strategy to counter the rapidly evolving SARS-CoV-2 variants.